Death within the first 24 hours of admission among newborn infants aged less than 24 hours in a Nigerian Special Care Baby Unit: Role of significant hypothermia and hypoglycaemia - Tinuade Ogunlesi (Mashhad University of Medical Sciences, 2015)
Background: Neonatal deaths mostly occur within the first one week and first 24 hours of life from a variety of conditions. Objective: To examine the role of significant hypothermia and hypoglycaemia, in addition to some other factors, in neonatal mortality occurring within the first 24 hours of admission.Methods: A prospective study of newborn infants hospitalized within the first 24 hours of life in a Nigerian Special Care Baby Unit. The axillary temperature and serum glucose at the point of admission were recorded for consecutive admissions. Significant hypothermia (axillary temperature < 36C) and hypoglycaemia (random blood glucose < 40mg/dl) were related to the risk of death within the first 24 hours of admission using bivariate and multivariate analysis. Results: Out of 277 infants, 24.2% and 27.3% had significant hypothermia and hypoglycaemia respectively. The overall mortality rate was 21.6% (49/227); 38.8% (19/49) of the infants died within the first 24 hours of admission. The Case Fatality Rate (CFR) among infants with co-existing significant hypothermia and hypoglycaemia was 41.2% compared to 0.9% among infants with neither significant hypothermia nor hypoglycaemia. Death within the first 24 hours of admission was significantly associated with hypoglycaemia, significant hypothermia, asphyxia and apnea using both bivariate and multivariate analysis. Conclusion: Deaths within the first 24 hours of admission, among infants admitted within the first 24 hours of life constituted close to 40% of all neonatal deaths in the present study with significant hypothermia and hypoglycaemia as major independent contributors.